2012
DOI: 10.4269/ajtmh.2012.12-0204
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Beliefs About Heredity with Preventive and Interpersonal Behaviors in Communities Affected by Podoconiosis in Rural Ethiopia

Abstract: Abstract. Little is known about how beliefs about heredity as a cause of health conditions might influence preventive and interpersonal behaviors among those individuals with low genetic and health literacy. We explored causal beliefs about podoconiosis, a neglected tropical disease (NTD) endemic in Ethiopia. Podoconiosis clusters in families but can be prevented if individuals at genetically high risk wear shoes consistently. Adults (N = 242) from four rural Ethiopian communities participated in qualitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 36 publications
8
56
0
Order By: Relevance
“…25 We found that the caregiver's gender was significantly associated with reported shoe wearing by the index child. Female caregivers reported less regular shoe wearing among index children than male caregivers.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…25 We found that the caregiver's gender was significantly associated with reported shoe wearing by the index child. Female caregivers reported less regular shoe wearing among index children than male caregivers.…”
Section: Discussionmentioning
confidence: 66%
“…Consistent with our qualitative study, affected respondents were less likely to recognize heredity as a cause of podoconiosis than those who were not affected by the condition. 25 Beliefs about heredity were negatively associated with reported shoe wearing of the index child in affected households. When these beliefs were coded for accuracy, affected individuals were more accurate in their knowledge than unaffected respondents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations